I6 Risk of hospitalisation with fever following menb vaccination: self-controlled case series analysis. (12th March 2018) - Murdoch, H; Wallace, L; Bishop, J; Robertson, C; Cameron, JC
Abstract : Aims: To investigate a possible association between fever admissions and 4 component Meningococcal B (4CMenB). Methods: 4CMenB is given at 8 and 16 weeks in the first year of life. Children included in this study were aged under 1 year in Scotland pre- and post-introduction of 4CMenB vaccine (pre—September 2014 to August 2015 and post—September 2015 to June 2016). The main outcome measure was hospitalisation for fever attributable to 4CMenB vaccine. Analysis was by self-controlled case series using linked routinely collected healthcare data, where the risk period was the 3 days immediately following receipt of a vaccine dose. Results: The post-introduction model showed an increased risk in the 3 days after dose 1 (relative incidence (RI), 10.78; 95% CI: 8.31 to 14.00) and dose 3 (RI, 9.80; 95% CI: 7.10 to 13.62), with a smaller increased risk after dose 2 (RI, 2.20; 95% CI: 1.27 to 3.82). The magnitude of these effects was greater than in the pre-introduction model. The attributable fractions were 90.7%, 54.8% and 89.7%, equating to 162, 14 and 84 vaccine attributable cases per 1 00 000 doses, respectively. This is equivalent to 102 extra hospitalisations in Scotland annually, based on a birth cohort of 55 100 and extrapolated to 1430 across the UK based on a birth cohort of 7 77 165. Conclusion: There is an increased risk of hospital admission with fever within 3 days of the routine childhood immunisations at 8 and 16 weeks following introduction of 4CMenB vaccine. The results indicate that further understanding of the current use of prophylactic paracetamol is needed. Communication to parents and health professionals has been re-examined, and guidance on the use of prophylactic paracetamol reinforced.